PERFORMANCE ANALYSIS OF HOSPITALITY INDUSTRY: CASE STUDY OF DIAFAN HOTEL WONOGIRI - Diafan, Dionisius Baren; Handayati, Yuanita (Journal of Business and Management, 2017)
Abstract. As a tourist place, Indonesia is supported by beautiful natural scenery and unique culture. Actually, most of Indonesia's revenue comes from the tourism sector. Wonogiri as one of the regencies in Central Java is one of the tourist attractions. Unfortunately, all the facilities and tourist attractions here need improvement, such as hotels. Hotels in Wonogiri need attention on the performance management system. One of them is Diafan Hotel. To improve this hotel, the Balanced Scorecard analysis will be applied. Because the Balanced Scorecard is used as a benchmark not only from the financial aspect but also from non-financial aspects, through four perspectives: financial perspective, customer perspective, internal business perspective, and learning and growth perspective. The author will assess performance through literature studies and employee interviews from the Diafan Hotel. Since 2014 the performance of the Diafan Hotel has not increased, this is indicated by a stable financial condition. Diafan Hotel management has never applied KPI to create targets. This occurs because when targeting at Diafan Hotel uses the classical method that estimates are based on perceptions of top management duties, while defining KPIs must be measured either by the Balanced Scorecard (BSC) method, which makes the KPI more realistic and achievable by the company during periods such as which are expected. Beginning with the gathering of strategic information based on interviews with the company then the literature study, then processing them into data based on Balanced Scorecard research. At this point, it is known that the Diafan Hotel is in the internal-external matrix cell V (growth) analysis diagram. So, this hotel needs to implement growth strategy through horizontal integration. The strategy has 5 strategic goals, 16 strategic targets, 24 Key Performance Indicators (KPIs), and  23  strategic initiatives. All  this  as  a  form of  guidance for  the  performance management system of Diafan Hotel. Keywords: Diafan Hotel, Hospitality Industry, Balanced Scorecard, Performance, Management System, Tourism